MILITARY MEDIATION AS A NEW FORM OF NEGOTIATION PROCESS - Слюсаренко, Ольга (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d . In today's world, where the number of armed conflicts continues to rise, the issue of their resolution is becoming increasingly urgent. According to the international online platform Rule of Law in Armed Conflicts (RULAC), there are currently over 110 armed conflicts worldwide involving at least 55 states and more than 70 non-state armed actors. Military mediation is an emerging branch of negotiation aimed at resolving conflicts within the military domain. The use of military mediation enables de-escalation of violence and contributes to the achievement of peace agreements. This article explores the concept of military mediation, its key characteristics, methods, and effectiveness under contemporary conditions. M e t h o d s . he study is based on the application of the following scientific methods: Literature analysis – the theoretical foundations of military mediation and its implementation in international conflict resolution; Comparative method – juxtaposition of various approaches to armed conflict resolution through mediation; Modelling method – development of potential scenarios for applying military mediation in current conflicts; Empirical method – analysis of real-world cases of successful implementation of military mediation in the history of international relations. R e s u l t s . The research summarises and systematises data concerning: the classification of armed conflicts and their impact on international security; methods of negotiation within the military domain and their specific features; the use of military mediation in conflict resolution; international experience in the application of military mediation across various countries; practical aspects of military mediation, its effectiveness, and prospects for development. C o n c l u s i o n s . Military mediation is an effective tool for preventing the escalation of armed conflicts, allowing for the achievement of compromises and the signing of peace agreements. It holds significant potential for conflict resolution both at the international and national levels. The core principles of military mediation include neutrality, confidentiality, flexibility, and adherence to international humanitarian law. Notable examples of military mediation include the peace process in Colombia, negotiations in Libya, Sudan, Cyprus, and others. The successful application of military mediation requires the development of professional training programmes for military mediators and the implementation of new approaches to peaceful conflict resolution.

В с т у п . У сучасному світі, де кількість збройних конфліктів зростає, питання їх урегулювання стає дедалі актуальнішим. За даними міжнародного онлайн-порталу "Верховенство права у збройних конфліктах (RULAC)", нині у світі зафіксовано понад 110 збройних конфліктів, у яких беруть участь щонайменше 55 держав і понад 70 збройних недержавних суб'єктів. Військова медіація є новим напрямом у переговорних процесах, що спрямований на врегулювання конфліктів у військовій сфері. Застосування військової медіації дає змогу уникати ескалації насильства та сприяє досягненню мирних угод. У цій статті розглянуто концепцію військової медіації, її особливості, методи й ефективність у сучасних умовах. М е т о д и . Дослідження базується на таких наукових методах, як-от: аналіз літератури – вивчення теоретичних основ військової медіації та досвіду її застосування у міжнародних конфліктах; порівняльний метод – зіставлення різних підходів до розв'язання збройних конфліктів за допомогою медіації; метод моделювання – розроблення можливих сценаріїв застосування військової медіації у сучасних конфліктах; емпіричний метод – аналіз реальних випадків успішного застосування військової медіації в історії міжнародних відносин. Р е з у л ь т а т и . У процесі дослідження узагальнено й систематизовано дані щодо: класифікації збройних конфліктів та їх впливу на міжнародну безпеку; методів переговорів у військовій сфері та їх особливостей; використання військової медіації для врегулювання конфліктів; досвіду застосування військової медіації у різних країнах; практичних аспектів військової медіації, її ефективності та перспектив розвитку. В и с н о в к и . Військова медіація є ефективним інструментом запобігання ескалації збройних конфліктів, що дає змогу знаходити компроміси й досягати мирних угод. Військова медіація має значний потенціал у розв'язанні конфліктів як на міжнародному, так і національному рівнях. Основними принципами військової медіації є нейтральність, конфіденційність, гнучкість і дотримання міжнародного гуманітарного права. Успішними прикладами військової медіації можуть слугувати мирний процес у Колумбії, переговори в Лівії, Судані, Кіпрі тощо. Використання військової медіації потребує розвитку професійної підготовки військових медіаторів і впровадження нових підходів до мирного врегулювання конфліктів.
ВІЙСЬКОВА МЕДІАЦІЯ ЯК НОВИЙ ВИД ПЕРЕГОВОРНОГО ПРОЦЕСУ
Keywords: військова медіація; збройний конфлікт; переговорний процес; міжнародне право; мирне врегулювання; дипломатія; військовий медіатор; медіація; медіаційна процедура; посередництво; сторони; що конфліктують; медіатор (посередник); примирення; військова медіація медіація військове право; military mediation; armed conflict; negotiation process; international law; peaceful settlement; diplomacy; military mediator; mediation; mediation procedure; third-party intervention; conflicting parties; mediator; reconciliation